Accelerating Digitalization in the Sharia Economy and Finance for Inclusive and Sustainable Growth in the Post-Pandemic Recovery - Perry Warjiyo (Journal of Islamic Monetary Economics and Finance, 2024)
This paper is based on a keynote speech delivered at The 9th International Islamic Monetary Economics and Finance Conference (9th IIMEFC). As a keynote contribution, this article does not include a formal abstract.